Mahuang Fuzi Xixin Decoction Ameliorates Allergic Rhinitis in Rats by Regulating the Gut Microbiota and Th17/Treg Balance. (25th May 2020) - Liang, Xiao; Liu, Chang-Shun; Wei, Xiao-Han; Xia, Ting; Chen, Fei-Long; Tang, Qing-Fa; Ren, Meng-Yue; Tan, Xiao-Mei
Abstract : Mahuang Fuzi Xixin Decoction (MFXD), a Chinese traditional herbal formulation, has been used to treat allergic rhinitis (AR) in China for centuries. However, the mechanism underlying its effect on AR is unclear. This study investigated the mechanism underlying the therapeutic effects of MFXD on AR. Ovalbumin-induced AR rat models were established, which were then treated with MFXD for 14 days. Symptom scores of AR were calculated. The structure of the gut microbiota was analyzed by 16S rRNA gene sequencing and qPCR. Short-chain fatty acid (SCFA) content in rat stool and serum was determined by GC-MS. Inflammatory and immunological responses were assessed by histopathology, ELISA, flow cytometry, and western blotting. Our study demonstrated that MFXD reduced the symptom scores of AR and serum IgE and histamine levels. MFXD treatment restored the diversity of the gut microbiota: it increased the abundance of Firmicutes and Bacteroidetes and decreased the abundance of Proteobacteria and Cyanobacteria. MFXD treatment also increased SCFA content, including that of acetate, propionate, and butyrate. Additionally, MFXD administration downregulated the number of Th17 cells and the levels of the Th17-related cytokines IL-17 and ROR γ t. By contrast, there was an increase in the number of Treg cells and the levels of the Treg-related cytokines IL-10 and Foxp3. MFXD and butyrate increased the levels of ZO-1 in the colon. This study indicated MFXD exerts therapeutic effects against AR, possibly by regulating the gut microbial composition and Th17/Treg balance.